Analysis of The Effect of Corporate Governance on Company Performance with Working Capital as A Mediating Variable (Study on Manufacturing Companies in Indonesia) - Ardira, Givantoro Agma; Hersugondo, Hersugondo (Jurnal Penelitian Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of Corporate Governance (CG) consisting of Board Independence (BI), Board Diversity (BD), Return on Assets (ROA), and Return on Equity (ROE) mediated by the Working Capital (WC) at Indonesia Manufacture Company during the current year 2019–2021. Purposive sampling method was used to determine the number of research samples. With a total sample of 63 samples from 2019–2021. The analytical technique used is multiple linear regression for each research model with the SPSS:25 program which previously passed the classical assumption test. The results in this study, BI has a positive and not significant effect on WC and BD has a positive and significant effect on WC. Variable BI has a positive and not significant effect. ROA and BD have a positive and not significant effect on ROA and WC has no effect on ROA then finally in the third model the BD has a positive and significant effect on ROE. Variable BD has a positive and significant effect on ROE and then the last variable WC has no effect on ROE.Keywords:Corporate Governance, Working Capital, Firm performance